Redox‐Active Functional Electrolyte for High‐Performance Seawater Batteries. Issue 9 (27th February 2020) - Lee, Seyoung; Cho, Il Young; Kim, Dowan; Park, Nam Kyu; Park, Jaehyun; Kim, Yongil; Kang, Seok Ju; Kim, Youngsik; Hong, Sung You
Abstract: Rechargeable seawater batteries have gained recognition as key sustainable electrochemical systems by employing the near‐infinite and eco‐friendly catholyte seawater. However, their practical applications have been limited owing to the low chemical and electrochemical stability of the anode component. Herein, a stability‐secured approach was developed by using sodium‐biphenyl‐dimethoxyethane solution as a redox‐active functional anolyte for high‐performance seawater batteries. This anolyte system shows high electrochemical stability, superior cycle performance, and cost‐effectiveness over conventional electrolyte systems. Abstract : Beyond the sea : Rechargeable seawater batteries have been attracting large attention by employing infinite and eco‐friendly seawater catholyte. Here, SWBs are reported based on the redox‐active functional anolyte Na‐biphenyl‐dimethoxyethane, which can be used as both liquid anode and electrolyte in the anode part to allow the electrochemical reversibility and long cycle performance.